A proteção constitucional das crianças e dos adolescentes: uma análise da (des)juridicização fáctica no município de Maceió - Araújo, Ana Luiza Nogueira de (2009)
The scope of this paper is to assess how far the Brazilian constitution goes in protecting the fundamental rights of children and teenagers. Such is accomplished through an axiologic, dogmatic, and sociological perspective. This latter aspect mainly concerns the services provided by the public sector in the city of Maceió. By examining the Brazilian juridical framework, the first perspective is aimed at showing the paradigmatic change when approaching the rights of children and teens. A juridical analysis of the topic may effectively be made through the prism of the paradigmatic crisis. After the promulgation of the new Federal Constitution, the so-called old paradigm, representing the entire legislative output pertaining to the doctrine of irregular situation, was superseded by a new system based on popular participation and social mobilization. Emphasis is also given to the constitutional regime and its repercussion upon ordinary legislation concerning the rights of children and teens. It begins with the broad concept of fundamental rights and of resolving the dichotomy between rights of the individual, of defense, and social rights. The paper also analyzes the modern state system in an attempt to ensure the effectiveness of that which is constitutionally accepted, with special attention given to the situation encountered in the city of Maceió, primarily on how to deal with the public and those mechanisms that afford special protection. Its inefficacy is thus made clear in view of incipient jurisprudence to secure absolute priority, in addition to difficulties in the organizational structure of childhood protection as well as the lack of funds and qualified personnel. Statistics about violence against children and teens perpetrated by adults (criminally imputable) in the state capital of Alagoas have also attested to the need for public intervention.